Generation Z Students' Perceptions of Arabic Language Learning Content on TikTok and Their Interest in Learning Arabic: تصورات طلاب جيل "Z" تجاه المحتوى التعليمي للغة العربية على منصة تيك توك وعلاقتها باهتمامهم بتعلم اللغة العربية - Nurul Hadriyah; Dian Risky Amalia; Nailul Izzah (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2026)
Generation Z lives in a digital age that has made social media, including TikTok, one of their primary sources of information and learning. Therefore, it is necessary to examine the impact of TikTok use on students’ interest in learning Arabic. This study aims to determine the level of interest in learning Arabic among Generation Z students who use TikTok as a learning medium. This study employs a quantitative research design with a correlational approach. The research subjects consist of 30 eleventh-grade students selected using purposive sampling. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics to describe the research variables and the Pearson Product-Moment correlation test with the aid of IBM SPSS Statistics to determine the relationship between Arabic educational content on TikTok and students’ interest in learning. The results of the study indicate a positive and significant relationship between the use of Arabic educational content on TikTok and students’ interest in learning Arabic (r = 0.599; p < 0.05), which falls into the moderate relationship category. These findings indicate that the more positively TikTok is utilized as a learning medium, the higher students’ interest in learning Arabic becomes. The implication of this research is that TikTok can be utilized as an engaging and appropriate medium to support Arabic language learning, particularly one that aligns with the characteristics of Generation Z. Therefore, teachers are advised to integrate social media-based educational content into the learning process to enhance students’ interest in learning.